Aplikasi Media Belajar Menulis Huruf dan Angka Bilingual Berbasis Web - Wan Yuliyanti; Fathurrahmani; Apriliyana (Jurnal Humaniora Teknologi, 2022)
Learning media is now very developed where everyone can learn anywhere by using a smartphone to get the material or learning they want to know. Everyone needs learning usually starting from the basic learning taught since childhood. Where basic learning starts from the introduction and writing of letters and numbers. It is necessary to know how to write letters and numbers so that the writing can be done more effectively. A child who is just learning to write is likely to have difficulty in recognizing letters and numbers. So that the author provides solutions, among others, by building a web-based bilingual letters and numbers learning media application to overcome these problems. This application is built with the waterfall method and uses PHP and MySQL programming languages. This web-based application bilingual learning media of writing letters and numbers can help parents in teaching their children in terms of how to write letters and numbers that are good, correct, easy and fun. This application has interactive videos so that it is more interesting and educative. In addition, this application uses two languages, Indonesian and English. Where when the numbers and letters are clicked, the sound will be heard in Indonesian and English. The data that has been successfully collected is in the form of letters and numbers taken from books, journals, articles, websites.